Variação pronominal de primeira pessoa do plural: "nós" e "a gente" na Cidade de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The subject pronoun variation nós and a gente has already been studied by many variationist researchers in the area of Brazilian Portuguese (henceforth BP) (LOPES, 1998, 2003a, 2003b, 2004, 2007; RUBIO, 2011; SOUZA; BOTASSINI, 2009; ZILLES, 2007 among others) specially for having verified the insertion of the form a gente as a substitute for we. This study is based on the theory of Labov’s Variationist Sociolinguistics (LABOV, 2008; WEINREICH; LABOV; HERZOG, 2006), as well as on the assumptions about classical grammaticalization with the goal to understand the crystallization process of the noun gente until the pronominal form a gente, still based on studies of variation of both forms, (CASTILHO, 1997, 2016; LOPES, 1998, 2003a, 2003b, 2004; VIANNA; LOPES, 2015, among others). Based on this theme, the present research intends to investigate the first person plural pronominal variation in the speech community of the town of Goiás, aiming at understanding the influence of linguistic and social aspects in the use the forms. For the analysis, twenty-four informants, of two different samples, stratified by gender and age group, were selected. Twelve interviews were extracted from the database of the Functionalist Studies Group (GEF / UFG), Federal University of Goiás, as follows: 6 informants of each sex (3 in each age profile), divided into two age groups (25 to 43 years and 44 years and above); and other 12 interviews were recently conducted, constituting the Sociolinco database, linked to the Study and Research Group on Sociolinguistics of the State University of Goiás, Campus Cora Coralina, also with 6 informants of each gender (3 in each age profile), with ages between 25 and 40 years and 41 and 60 years. Most informants are born in the town or came to live in the place up to 2 years of age and have between zero and four years of schooling. With the aid of the GoldVarb X program, the data were treated statistically. For this, it was decided to perform three main rounds: the first, with the joining of all data (Corpus GEF/UFG and Sociolinco). Then, two more rounds were performed, one for each separate sample, thus performing a real-time analysis, based on a trend study. Thus, the results pointed to two different situations: in the first corpus, constituted with the GEF/UFG interviews, the use of nós is more frequent. While in the data obtained in the Sociolinco interviews, the pronoun a gente stands out. For this reason, it may be pointed out that, just as in BP, the pronominal form a gente, in the context of the vilaboense speech, is in a process of linguistic change, which does not cause nós to fall into disuse, which configure it as a stable variation.
First Person Plural Variation: "nós" and "a gente" in the town of Goiás
Keywords: Sociolinguística variacionista; Gramaticalização; Cidade de Goiás; Variationist sociolinguistics; Grammaticalization; Goiás town; LINGUISTICA, LETRAS E ARTES